Mewujudkan UMKM Mandiri Melalui Integrated Online Marketing di Desa Punggul Sidoarjo - Anang Kistyanto; Ulil Hartono; Fandi Fathoni; Yuyun Isbanah; R.A. Sista Paramita (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
Punggul Village is known as “Hat Village” because it has Hat and Bag SMEs, but it is not well organized compared to the Tanggulangin bag industry. The absence of a cooperative has caused them to work alone to make and market their products. The marketing aspect is still a concern in this program. SME Bags and Hats in Punggul village have received several pieces of training. They have made a website/blog to display their products, but not optimal because SME owners can not add photos of their new products and fill out the website. Currently, seeing that many people are more familiar with gadgets and the internet, the Punggul village hat bag UKM will be given knowledge and understanding of integrated online marketing through the integration of marketing communications by utilizing Instagram and Whatsapp businesses. The Punggul village bag and hat UKM was given training in digital marketing, making WhatsApp business and Instagram, and designing the advertisement media, such as business cards containing product descriptions and product lists. The training result shows that the average participant satisfaction response is in the high category, which means that participants are generally satisfied with this training activity. Regarding digital marketing, it becomes easier for partners to always be active in managing their social media (Instagram and WhatsApp business), including filling out content and communicating with customers.